Lithium Fluoride Based Electron Contacts for High Efficiency n‐Type Crystalline Silicon Solar Cells. Issue 14 (25th May 2016) - Bullock, James; Zheng, Peiting; Jeangros, Quentin; Tosun, Mahmut; Hettick, Mark; Sutter‐Fella, Carolin M.; Wan, Yimao; Allen, Thomas; Yan, Di; Macdonald, Daniel; De Wolf, Stefaan; Hessler‐Wyser, Aïcha; et al.
Abstract : Low‐resistance contact to lightly doped n‐type crystalline silicon (c‐Si) has long been recognized as technologically challenging due to the pervasive Fermi‐level pinning effect. This has hindered the development of certain devices such as n‐type c‐Si solar cells made with partial rear contacts (PRC) directly to the lowly doped c‐Si wafer. Here, a simple and robust process is demonstrated for achieving mΩ cm 2 scale contact resistivities on lightly doped n‐type c‐Si via a lithium fluoride/aluminum contact. The realization of this low‐resistance contact enables the fabrication of a first‐of‐its‐kind high‐efficiency n‐type PRC solar cell. The electron contact of this cell is made to less than 1% of the rear surface area, reducing the impact of contact recombination and optical losses, permitting a power conversion efficiency of greater than 20% in the initial proof‐of‐concept stage. The implementation of the LiF x /Al contact mitigates the need for the costly high‐temperature phosphorus diffusion, typically implemented in such a cell design to nullify the issue of Fermi level pinning at the electron contact. The timing of this demonstration is significant, given the ongoing transition from p‐type to n‐type c‐Si solar cell architectures, together with the increased adoption of advanced PRC device structures within the c‐Si photovoltaic industry. Abstract : Exceptionally low contact resistivity is demonstrated on lightly doped (5 × 10 15 cm −3 ) n‐type silicon via a nanometer thin lithium fluoride (LiF x ) interlayer. This advancement enables the fabrication of a first‐of‐its‐kind n‐type silicon solar cell with a LiF x /Al partial rear contact made to less than 1% of the cell's area. An efficiency of over 20% is achieved at the proof‐of‐concept stage.